Politik Hukum Ketenagakerjaan : Konstruksi Hukum Perjanjian Kerja Mitra (PKM) Pada Outsourcing - Marlinah (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2021)
Companies nowadays prefer to use partner work agreements because they think that these agreements are more profitable for business actors, whereas in labour law there are only two (2) types of work agreements, namely specific time work agreements and indefinite time work agreements. This research aims to know and analyse the legal relationship of the parties in a partner work agreement in outsourcing, and the form of legal protection given to workers with partner work agreements in outsourcing. The method used is the legal research method which aims to achieve a solution to the legal issues and problems that arise therein, so that the result to be achieved then is to provide a prescription of what should be on the issue raised. A partner work agreement gives rise to a legal relationship between the outsourcing party and the worker, which legal relationship causes legal consequences, namely the rights and obligations of each party involved, namely the worker and the outsourcing party. There are two (2) types of legal protection for workers, namely preventive protection and refressive protection.